S&B* Mining Stewardship in Milos Island - Stefanakis, Michalis (Bulletin of the Geological Society of Greece, 2018)
In this article the stewardship activities to ensure minimization of environmental impacts and health & safety risks arising from the exploration, extraction, processing and loading-transportation of bentonite and perlite currently mined by S&B are described. This is defined as “process stewardship”. Limited reference is also made to “product stewardship” activities associated with the downstream use of said products across their life cycle. The contribution made to local community and the infrastructure development to support parallel development of tourism and other activities is also described. The S&B mining stewardship in Milos Island subscribes fully to the S&B sustainable development goal and targets, to which reference is also made.